Measured growth and tree biomass estimates of Terminalia ivorensis in the three years after thinning to different densities in an agrisilvicultural system in southern Cameroon - Norgrove, L.; Hauser, S. (Elsevier, 2002)
Tree growth was monitored for 3 years in two Terminalia ivorensis (A) Chev (Combretaceae) plantations in the humid tropics of southern Cameroon. The plantations were 6 and 17 years old, when they were each thinned to two stand densities (SDs) and understorey food crops were introduced. The SD treatments were also compared with unslashed, non-cropped ‘control’ plots. As in ‘taungya’ systems, slashing the undergrowth, and planting food crops resulted in greater increases in stem cross-sectional area at breast height (m2 per tree per year) and greater estimated biomass accumulation in both plantations, compared with control plots. Within SD treatments, growth increments per tree were similar between years, resulting in highly significant linear regressions. Within treatments, regression coefficients were similar across plantations: for the high SD, 93 in the younger and 73 in the older plantation; for the control, 38 in the younger and 34 in the older plantation. These results suggest that, at least between 6 and 20 years of age, T. ivorensis has a linear, rather than a sigmoid or ε-function-shaped growth pattern and that the increased growth rate in response to thinning is maintained for the following years. Estimated carbon accumulation in all tree species greater than 14 cm in girth in the high SD treatment was 71 Mg C ha−1 by year 9 in the younger plantation and 84 Mg C ha−1 by year 20 in the older plantation.